ANALISIS TEKNO EKONOMI PERANCANGAN 4G LTE DI KABUPATEN BANYUMAS - Abny Irawan; Alfin Hikmaturokhman; Dadiek Pranindito (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2018)
Banyumas Regency has a very rapid development with the progress in knowledge education. The development of Banyumas Regency, it is also necessary to improve the telecommunication service that is feasible. Indosat is one of the operators of 4G LTE technology developers using 1800Mhz frequency. Planning is using atoll software with reference to downlink, uplink and volume requirement of data needed by considering demography factor and projection of user in Banyumas Regency. The calculation of LTE technology deployment scheme based on Banyumas Regency area coverage requires 124 sites, while calculation based on capacity needs 71 ??sites in 2016. Simulation result using atoll software shows average RSRP value -80.9dBm and SINR value 0.64dB. Services at simulation atoll software that used by customers in Banyumas District is IMS Signaling 14,639 people, streaming media 34,348 people, video phone 65,731 people, real time gaming 20,637 people, video conference 66,325 people and voice over IP service 134,331 people. CAPEX covers is eNodeB device costs, license, Installation and loan capital. OPEX includes Operational & Maintenance, Rental backhaul, HR cost, Interconnection fee, marketing fee, general administration fee & Frequency BHP. Depression assumption for 10 years. The funding structure is the assumption of 60% loan & 40% own capital. The loan interest rate is 7.5% per annum with the assumption of a 5 year loan repayment. Annual tax of 25%. WACC of 12.5%. Cost benefit calculation yields 3% IRR and NPV Rp-8,729,606,072. So the design of LTE deployment in Banyumas regency for 15 years has not received a payback period or is still a loss.